Numerical design of polycapillary X-ray optics as both a focusing X-ray lens and a vacuum window. (November 2015) - Jiang, Bowen; Liu, Zhiguo; Sun, Weiyuan; Sun, Xuepeng; Li, Fangzuo; Ma, Yongzhong; Sun, Tianxi
Abstract: Polycapillary X-ray optics as a new application is proposed to be used as both a focusing X-ray lens and a vacuum window placed in the middle part which connected X-ray source in a clearly high vacuum with sample or detector in a moderate vacuum. Numerical results showed that such polycapillary X-ray optics had a low vacuum conductance, and it could be accordingly used as both such vacuum window for an X-ray source in a clearly high vacuum and a focusing X-ray lens at the same time. Highlights: Polycapillary X-ray optics is proposed to be used as a vacuum window. Polycapillary has a low vacuum conductance. Polycapillary can be used simultaneously as a vacuum window and focusing X-ray lens.